Newton's Third Rule and the Experimental Argument for Universal Gravity. - Belkind, Ori (HOPOS: The International Society for the History of Philosophy of Science)
Domski's central argument is that Newton does not think that gravity passes, or needs to pass, the invariance criterion to be considered a universal quality. According to Domski's interpretation, Newton is carrying out a large-scale inductive argument, claiming that if gravity is present in all observable bodies, it is present in all bodies. Newton's third rule is an important methodological statement in Newton's I Principia i , because he takes it to be required for demonstrating the universal nature of gravity. So Newton does not take the invariance criterion to differentiate between inertia and gravity; he rather takes the two qualities to be analogous in how they obey the invariance criterion.